Rapid detection and identification of Legionella pneumophila by a membrane immunoassay. - Bérubé, A (1989)
Legionella pneumophila was detected and identified by an immunoblot assay using a monoclonal antibody specific to serogroups 1 to 8. Samples containing L. pneumophila were plated on buffered charcoal yeast extract agar supplemented with glycine, vancomycin, and polymyxin B. After incubation at 35 degrees C for 3 days, colonies were transferred to nitrocellulose membranes by blotting. Simultaneous detection and identification of L. pneumophila were done by treating the membrane with the monoclonal antibody and a peroxidase conjugate to mouse immunoglobulins. A diffuse cross-reaction was observed with Pseudomonas fluorescens colonies, but this was a low-level reaction that could easily be differentiated from the strong specific reactions to L. pneumophila.